Perspectives on Germany’s Welfare Reform (“Bürgergeld”) - Christian Merkl (Wirtschaftsdienst)
Abstract The Hartz IV labour market reform in 2005 triggered a substantial reduction in unemployment in Germany. At the same time, it reduced social welfare for the long-term unemployed and increased uncertainty for the employed. The proposed reform by the new government (“Bürgergeld”) will adjust the German welfare system moderately towards more social insurance. This article argues that the associated negative employment effects can be minimised by requiring appropriate participation from unemployed and by preventing new paths to early retirement. In addition, the article further discusses potential reforms to better reconcile employment incentives and social insurance.